AKTIVITAS ANTIOKSIDAN FRAKSI-FRAKSI MODEL DARI PRODUK REAKSI MAILLARD - Rosida, Dedin F; CH, Wijaya; A, Apriyantono; FR, Zakaria (REKAPANGAN, 2010)
The Â oxidative Â browning Â is Â considered Â to Â have Â a Â contribute Â to Â the Â flavor, Â antioxidativeÂ activity Â and Â color Â of Â food. Â As Â a Â result Â of Â this Â Maillard Â reaction, Â a Â variety Â of Â by Â products,Â intermediates and brown pigmens (melanoidins) are produced. The objectives of this researchÂ was to study the effect of heating and sugar addition of Model to Â antioxidant activity. Â The Â research is model Â system of Â Maillard Â reaction Â products Â were Â too Â made Â from Â sugarÂ and Â amino Â acids Â and Â adjusted Â to Â the Â soysauce Â preparation. The Â model Â contents Â of Â glucose âÂ glycine - cysteine; glucose â glycine â cysteine - phenylalanine; glucose â glycine â cysteine âÂ phenylalanine â isoleucine - tyrosine. The model were fractionated into molecular weight of 10Â kDa â Â 100 Â kDa Â by Â ultrafiltration. Â The Â fractions Â were Â characterized Â by Â  Â spectra Â profile Â ofÂ ultraviolet-visible. The antioxidant of fractions activity was evaluated by rancimat, DPPH(1,1-diphenyl-2-picrylhydrazyl), Â TBA Â value, Â ferric Â thio Â cyanate and Â hemolysis Â of Â erythrocyteÂ methods. Â The fractions of model can retard oxidation of oil and had DPPH radical of scavengingÂ activity especially both Fractions Â molecular weight >100 kDa (F1) and Â 30-100 kDa (F2), andÂ equal Â with Â the Â BHT Â antioxidant. Â Antioxidant Â activity Â of Â glucose-glycine-cysteine model Â byÂ rancimat and thio cyanate method showed Â the longest induction period for 15 hours and 72%Â antioxidant activity, whereas the radical DPPH scavenger activity for all model showed mostÂ equaly (60%). The fractions with molecular weight about 30-100 kDa (F2) resulted the highestÂ antioxidant activity. The fractions of model had antioxidant activity in food and biology system.Key Words : Maillard Reactions, Model, fractinationated, antioxidative activity